2018
DOI: 10.1111/jgs.15627
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Screening Tool to Predict Outcomes in Older Adults Undergoing Emergency General Surgery

Abstract: Objectives To determine whether the Flemish version of the Triage Risk Screening Tool (fTRST) can be used to accurately assess frailty in an emergency setting. Design Prospective observational study. Setting of a tertiary referral hospital. Patients All individuals aged 70 and older consecutively admitted to the emergency surgery unit with an urgent need for abdominal surgery between December 2015 and May 2016 who met inclusion criteria (N=110). Measurements Individuals were screened with the fTRST and additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 41 publications
(49 reference statements)
0
23
0
Order By: Relevance
“…The fTRST showed a trend to predict postoperative complications (p = 0.066) and was associated with prolonged postoperative LOS in univariable analysis (p = 0.006). A prospective study in emergency abdominal surgery observed an association between the fTRST (cut-off �2), postoperative complications and postoperative LOS [31].…”
Section: Discussionmentioning
confidence: 99%
“…The fTRST showed a trend to predict postoperative complications (p = 0.066) and was associated with prolonged postoperative LOS in univariable analysis (p = 0.006). A prospective study in emergency abdominal surgery observed an association between the fTRST (cut-off �2), postoperative complications and postoperative LOS [31].…”
Section: Discussionmentioning
confidence: 99%
“…The most important risk factor for functional decline is frailty [4,8,9]. The surgeon has few instruments to predict a postoperative functional loss in the busy emergency setting where a frailty assessment in not available or reliable [2,7,10]. A short frailty screening tool validated in a previous study, the Flemish version of the Triage Risk Screening Tool (fTRST), is effective in predicting 30-and 90-day morbidity and mortality after emergency abdominal surgery among older patients (≥70 years) [10].…”
Section: Introductionmentioning
confidence: 99%
“…The general surgical eld has already proposed a "Classi cation of Surgical Complications" by Clavien & Dindo. This standardized classi cation is nowadays widely applied in various surgical disciplines, and it is declared as an effective instrument for quality management [6,10,12,13,17,19,21,23,26]. The lack of such standardized classi cation is a subject of discussion over a long time in the neurosurgical eld.…”
Section: Introductionmentioning
confidence: 99%